PENERAPAN MANAJEMEN DAN STRATEGI BISNIS UNTUK MENINGKATAN PENDAPATAN PETANI SAYUR DI DESA WARNASARI, PANGALENGAN, KABUPATEN BANDUNG - Pratama, Agie Nugraha; Rofiq, Iwan Setiawan; Yulistiyono, Agus; Fauzi, Irman Ramdhan; Fibriyadi, Istna; Septriana, Derina Anggelika (POLITEKNIK LP3I JAKARTA, 2025)
The problem faced by farmers in Warnasari Village, Bandung, West Java, is that they generally rely on traditional knowledge in managing their vegetable farming business. Aspects of business management, such as production planning, financial record-keeping, and resource management, are not carried out systematically. The lack of business strategy implementation leads to low efficiency and income in farming. The method used in this Community Service activity is training or counseling. The goal of this activity is to increase awareness among the community about the importance of digitalizing vital family records through information provision. The process of implementing this activity starts from 1) Preparation, which includes needs analysis and coordination with the community, 2) Implementation, which includes preparing materials and providing information through lectures, 3) Evaluation, which involves creating follow-up plans. The conclusion of this activity is that farmers are expected to be able to manage their farming business more professionally, increase production efficiency, and expand market access, thereby significantly increasing their income. This activity is also expected to have a positive and sustainable impact on the welfare of vegetable farmers in Warnasari Village, and they plan to follow up with assistance from Politeknik LP3I Jakarta.